Comparative analysis of the biosimilar and innovative G-CSF modulated pathways on umbilical cord blood–derived mononuclear cells (2020)
Biosimilars of granulocyte colony-stimulating factor (G-CSF) have been routinely introduced into clinical practice. However, not functional genomics characterization has been performed yet in comparison with the innovator G-CSF. This study aimed to evaluate the transcriptomic changes in an in vitro model of umbilical cord blood cells (UBC) exposed to G-CSF for the identification of their modulated pathways. Umbilical cord blood cells-derived mononuclear cells (MNCs) were treated with biosimilar and innovator G-CSF for further gene expression profiling analysis using a microarray-based platform. Comparative analysis of biosimilar and innovator G-CSF gene expression signatures allowed us to identify the most commonly modulated pathways by both drugs. In brief, we observed predominantly upmodulation of transcripts related to PI3K-Akt, NF-kappaB, and tumor necrosis factor (TNF) signaling pathways as well as transcripts related to negative regulation of apoptotic process among others. In addition, hematopoietic colony-forming cell assays corroborate the G-CSF phenotypic effects over UBC-derived MNCs. In conclusion, our study suggests that G-CSF impacts UBC-derived cells through the modulation of several signaling pathways associated with cell survival, migration, and proliferation. The concordance observed between biosimilar and innovator G-CSF emphasizes their similarity in regards to their specificity and biological responses.